Preparations of Silyl Anions - Pulikkottil, Feba T.; Balakrishnan, Venkadesh; Chandrasekaran, Revathi; Murugesan, Vetrivelan; Rasappan, Ramesh (Synthesis, 2024)
This review collates synthetic procedures for the synthesis of different silyl anions, which are valuable reagents for chemists, particularly in the field of organic synthesis and organometallic chemistry. This includes the preparation of silyl anions of lithium, sodium, potassium, rubidium, and cesium from group I metals and silyl anions of beryllium, magnesium, calcium, strontium, and barium from group II metals. Synthetic procedures for silyl anions of zirconium, hafnium, cadmium, and zinc are also covered. The synthesis of group XIII silyl anions of boron and aluminum is also highlighted.1 Introduction2 Silyl Anions of Group I Metals2.1 Silyllithium2.2 Silylsodium2.3 Silylpotassium2.4 Silylrubidium and Silylcesium3 Silyl Anions of Group II Metals3.1 Silylberyllium3.2 Silylmagnesium3.3 Silylcalcium, -strontium, and -barium4 Silyl Anions of Transition Metals4.1 Silylzirconium and -hafnium4.2 Silylcopper and -cuprates4.3 Silylzinc4.4 Disilylzinc4.5 Silylzincate4.6 Silylcadmium5 Silyl Pronucleophiles of Group XIII5.1 Silylboranes5.2 Silylaluminum6 Silyl Anions of Group XIV6.1 Disilane Synthesis7 Conclusions
Keywords: silyl anions; organosilane; disilane; silylmetal; silylborane; silyllithium